2023
DOI: 10.3389/fonc.2023.1151769
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of immune checkpoint inhibitors combined with chemotherapy in patients with extensive-stage small cell lung cancer: a systematic review and meta-analysis of randomized controlled trials

Abstract: ObjectiveMany clinical trials of immune checkpoint inhibitors (ICIs) in combination with chemotherapy in the first-line treatment of extensive-stage small cell lung cancer (ES-SCLC) have been initiated, but the conclusions of these trials are not identical. This meta-analysis aimed to comprehensively collect these randomized clinical controlled trials (RCTs) to evaluate the efficacy and safety of ICIs combined with chemotherapy in the first-line treatment of ES-SCLC.MethodsWe systematically searched PubMed, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The aforementioned studies have made significant contributions to the existing body of research on the cost-effectiveness analysis of diverse therapeutic approaches, thus offering valuable insights into the economic viability of ICIs as a treatment option for ES-SCLC. The economic implications of utilizing ICIs in combination with chemotherapy for ES-SCLC represent a crucial area of study, and the findings from these scholarly investigations shed light on the cost-effectiveness and feasibility of such treatment approaches (31). Further research is warranted to explore additional factors influencing the pharmacoeconomics of ES-SCLC treatments, taking into account various healthcare systems and cost thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned studies have made significant contributions to the existing body of research on the cost-effectiveness analysis of diverse therapeutic approaches, thus offering valuable insights into the economic viability of ICIs as a treatment option for ES-SCLC. The economic implications of utilizing ICIs in combination with chemotherapy for ES-SCLC represent a crucial area of study, and the findings from these scholarly investigations shed light on the cost-effectiveness and feasibility of such treatment approaches (31). Further research is warranted to explore additional factors influencing the pharmacoeconomics of ES-SCLC treatments, taking into account various healthcare systems and cost thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers reported that the addition of ICIs to standard of care benefits a greater number of patients, prolonging survival with a manageable toxicity profile [ 5 ]. Data from a recent systematic review and meta-analysis highlighted that although the addition of ICIs to standard chemotherapy result in significant improvements in PFS and OS for patients with lung cancer, a worse safety profile can be expected [more adverse drug reactions (ADRs) observed] [ 6 ]. Finally, their efficacy was also demonstrated in the treatment of some rare tumors, such as Merkel cell carcinoma, squamous cell carcinoma of the skin, thymic epithelial tumors, and gestational trophoblastic neoplasia, as recently highlighted by Guven et al.…”
Section: Introductionmentioning
confidence: 99%